Introduction of Mathematics Learning Media at the Elementary School in SD Inpres Teamate, Pallantikang Village, Pattallassang District, Gowa Regency - Andi Aswani; Dian Anggreni; Mei Cahaya; Agustan Syamsuddin; Ernawati Ernawati (Asosiasi Profesi Multimedia Indonesia, 2024)
Mathematics is one of the core subjects in elementary school and plays a significant role in the development of students' logical and analytical thinking abilities. Therefore, the need to be given guidance on the introduction of learning media in mathematics education at the elementary school level. This activity aims to introduce and integrate IT-based learning media into mathematics education at Teamate Inpres Elementary School in Pallantikang Village, Pattallassang District, Gowa Regency. The implementation method of the activity includes the development of materials, teacher training, and student mentoring using the Khan Academy and To DO Math platforms. The findings indicate positive involvement, with 90% student participation in the activity. Evaluation of the activity results reveals a significant improvement in the understanding of mathematical concepts, with 80% of students showing increased speed and accuracy in their responses. The benefits obtained include an increase in student interest in learning, improvement of teacher skills in managing IT-based learning, and enhanced collaboration between the school and the community. The conclusion of this activity emphasizes the role of IT-based learning media strategies in improving the quality of elementary-level mathematics education and strengthening community involvement in supporting educational innovation.